ISOLATION AND CHARACTERIZATION OF PROBIOTIC LACTIC ACID BACTERIA FROM MILK AND CURD SAMPLES - K. SUGANYA; T. MURUGAN; M. MURUGAN (International Journal of Pharma and Bio Sciences, 2013)
Probiotic bacteria are dietary supplements of live microorganisms thought to be healthy for the host organisms. In this study, lactic acid bacteria were isolated from 2 different curd and milk sample. A total of 20 strains were studied for their characterization, from that 2 potential strains Lactobacillus acidophilus and Lactobacillus casei were identified. The potential strains were studied by curd production, antibacterial and bacteriocidal activity also their antibiotic susceptibility. The quality of curd was analyzed by qualitatively and quantitatively by nutrient evaluation (CHO, protein, ash, lipid, etc.). The antibiotic resistance of potential strain was studied using Vancomycin, gentamycin, chloromphenicol, ciprofloxicine and cefataximide. PB1, PB3 shows the good resistance activity to the antibiotics. The curd produced by those strains has good quality and quantity of nutrients. Also the total viable count in curd was performed; it showed 13 - 15 X 10-7 (CFU) cells per ml of curd.